Trastorno negativista desafiante y su efecto en el rendimiento escolar en un niño - Vásconez Viscarra, Liliana Raquel (2019)
The present case study is focused on the Challenging Negativist Disorder and its effects on school performance in a child, starting from the conceptualization of the variables to define it as the manifestation of a frequent and persistent pattern of anger, irritability, discussion, disobedience or resentment towards parents or other authority figures. This behavior goes beyond normal behavior and appears due to different factors, in this case, by attitudes learned by the parents and that can harm the child causing significant disturbance in the different areas: family-school, emotional and behavioral. Sometimes it is difficult to recognize the difference between a child of a strong or emotional nature and a child with a challenging negativist disorder. It is normal to observe a negative behavior at certain stages of a child's development, so it is important to observe these behaviors so as not to misdiagnosis. The treatment of cognitive behavioral therapy in the challenging negativist disorder involves learning skills to help build positive family interactions and control problem behavior. The Diagnosis begins through the interview and the observation, making use of the clinical history and psychometric tests. The study of this case was carried out in the Particular Educational Unit “Padre Marcos Benetazzo” of the fifth year of basic of the Babahoyo Canton. The cognitive-behavioral approach was applied, with the collaboration of parents and teachers in the family and school environment